Al-Kalimāt Al-Indūnīysiyah Dzātu Aslin Araby Fī (KBBI) wā Al-Istifādah minhā fī Ta’līm Mahāroh Al-kitābah lī Indunīysiyīn- Harfu T Namūdzajan - Nurul Falah Elyandri; Arif Taufikurrohman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
إنّ اللغة العربية لقد انتشر انتشاراً بليغاً في أنحاء العالم، وكان دخول الإسلام إلى إندونيسيا من وسيلة تجارة وزيارة من العرب. وحمل الإسلام بعض الكلمات التي لا توجد من قبل عند الإندونيسيين وترك أثر كبيراً في لغتهم، فهدف هذه الدراسة لكشف الكلمات الإندونيسية التي لها أصل عربي الموجودة في المعجم الكبير (KBBI) حرف T وتحليلها، ومعرفة التغيرات بعد دخولها إلى اللغة الإندونيسية، وتمكن الاستفادة منها في تعليم مهارة الكتابة للإندونيسيين. إن هذه الدراسة تسلك على منهج الوصف تحليلي، وذلك أثبتت وجود تلك الكلمات في معجم اللغة الإندونيسية الكبير (KBBI) تقريبا مئة كلمة المبتدئة بحرف T، ومن هذه الكلمات تكمن تقسيمها إلى أربعة الأقسام، الأول: الكلمة العربية التي بقيت معانيها في اللغة الإندونيسية، الثاني: الكلمة العربية التي اتسعت معانيها في اللغة الإندونيسية، الثالث: الكلمة العربية التي ضاقت معانيها في اللغة الإندونيسية، والرابع: الكلمة العربية التي انتقلت معانيها في اللغة الإندونيسية، ووعرضها، والاستنتاج. وأتت الدراسة بوضع تلك الكلمات في التدريبات لتكون نموذجا مقترحا في تعليم مهارة الكتابة للإندونيسيين. Arabic has spread throughout the world, and in the past Islam entered Indonesia through trade brokers and visits from Arabia. And Islam carries several words that have not been discovered by Indonesians and has a great impact on their language. The purpose of this study is to reveal Indonesian vocabulary derived from Arabic vocabulary, which is found in the Big Indonesian Dictionary (KBBI) letter T and analyze it, to find out the changes after entering into Indonesian, and how to implicate them in teaching skills writing for Indonesian students. This research is based on the analytical description method, and this has proven the existence of these words in the Big Indonesian Dictionary (KBBI) about one hundred words, starting from the letter T and from these words are divided into four parts, first: Arabic word which means still in Indonesian, second: Arabic word which means expanded in Indonesian, third: Arabic word which means narrowed in Indonesian, and fourth: Arabic word which means moving in Indonesian, and its conclusions. This study places these words in practice as a recommended model for teaching Indonesian writing skills.